The Influence of Brand Signature and Brand Reputation on Brand Performance - Simbolon, Hartobela; Pratama, Raka Rizki; Yuliana, Lingga (Journal of Applied Business Administration, 2024)
This study uses the Kopi Kenangan brand as a case study to examine how brand signature and reputation affect brand performance. The study used a quantitative research design. Purposive sampling was the method of sampling. This survey comprised 214 respondents in total. Respondents are Indonesian-domiciled men and women between 17 and 55 who drink Kopi Kenangan and adhere to our criteria of following the most recent coffee news. Using Google Forms to distribute questionnaires, the data source employs primary data. This study uses closed-ended questions with a Likert scale with response categories of strongly disagree, disagree, agree, and highly agree. Partial Least Square is the data analysis method that makes use of the SmartPLS tool version 4.1.0.0. The study's findings support the first hypothesis, which states that brand signature influences brand performance. Conversely, the second hypothesis demonstrates that brand reputation influences brand performance.